Effect of White Noise on Sleep Quality Patient with Acute Myocardial Infarction - Susanti, Lise; Purnama, Agus; Susaldi, Susaldi (Griya Eka Sejahtera, 2025)
Background: Symptoms of acute myocardial infarction include chest pain radiating to the neck, jaw, shoulders and arms , as well as shortness of breath and stress , which can cause decreased sleep quality. Therapy given to overcome sleep quality disorders includes pharmacological and non-pharmacological therapy, including the use of complementary methods in the form of white noise therapy. This study aimed to determine whether there is an effect of white noise therapy on sleep quality in patients with acute myocardial infarction.Methods: This type of research is quantitative research with a non-equivalent control group design method or untreated control group design with pretest and posttest. The population of this study was 24 respondents , with sampling using non-probability sampling.Results: Based on the results of the study The average age of respondents was in the age range of 54.0 years and Pvalue of < , 001 < 0.05 with an effect size of 2.30 with an average value before white noise therapy was given as much as 33.3% and after white noise therapy was given to 100%.Conclusion: There is an effect of changes in sleep quality in patients with acute myocardial infarction at Amira Hospital in 2024 after being given white noise therapy.